2019
DOI: 10.1186/s41687-019-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-vigorous physical activity and health-related quality of life among Hispanic/Latino adults in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Background Physical activity is a modifiable healthy behavior that has been shown to positively influence health-related quality of life. However, research examining the link between physical activity and health-related quality of life among Hispanic/Latino adults is limited and inconsistent. The purpose of this study is to assess whether accelerometer-measured moderate-vigorous physical activity (MVPA) is associated with self-reported (a) mental health-related quality of life, and (b) physical he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…For mid adults, higher engagements in vigorous PA were also linked to higher QoL in physical health and psychological domain. This is interesting as in comparison to a Hispanic/Latino population reported in Vásquez et al (2019), vigorous PA was found only correlated with better physical health but not psychological related QoL, but in our study using Malaysian samples within the similar age range, vigorous PA was positively linked to both domains, consistent to findings reported in some previous studies (Kokandi et al, 2019; Puciato et al, 2018). For young adults, neither physical health nor psychological domain was significantly correlated with any level of PA.…”
Section: Discussionsupporting
confidence: 91%
“…For mid adults, higher engagements in vigorous PA were also linked to higher QoL in physical health and psychological domain. This is interesting as in comparison to a Hispanic/Latino population reported in Vásquez et al (2019), vigorous PA was found only correlated with better physical health but not psychological related QoL, but in our study using Malaysian samples within the similar age range, vigorous PA was positively linked to both domains, consistent to findings reported in some previous studies (Kokandi et al, 2019; Puciato et al, 2018). For young adults, neither physical health nor psychological domain was significantly correlated with any level of PA.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a 17-level cross-classification variable was constructed, where all combinations of Hispanic/Latino background and field center with inadequate sample size (N < 100) were pooled with the "mixed" category within that field center. Health-related quality of life was assessed with using the Short-Form 12 Health Survey (SF-12); the SF-12 mental and physical component summary scores were computed and standardized (to a mean of 50 and an SD of 10) to capture the mental health-related quality of life and the physical health-related quality of life, respectively (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that a range of demographic and psychosocial factors, such as older age, physical health [11,12], mental health symptoms, unhealthy behaviors (e.g., smoking, poor sleep) [13][14][15][16], and life stressors [17] are associated with lower QOL. Additionally, research among service members and veterans has shown that service-related factors, (e.g., deployment, service branch, pay grade, component, and combat injury), pre-existing physical health conditions (e.g., asthma and hypertension), and poor mental health (e.g., PTSD) are adversely associated with QOL [12,16,18].…”
Section: Introductionmentioning
confidence: 99%